(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The women who supported the Second Spanish Republic were socially constructed, even before the onset of the Civil War, either as a silenced myth or as a vociferous ideal. In exile, in prison, and in the streets, women who had been identified as reds during the Civil War, were subject to all kinds of oblivion and infamy in the time of Franco’s Spain. After the dictator’s death, these women were notoriously remembered and idealized through their own writing or by the work of scholars. I shall focus on testimonial narratives but will also briefly discuss other types of texts (poetry, novel, letters, and films) that complement the social construction of the identity of the Republican woman. The voices of this feminine silence are to be found somewhere between the veiled or open demonizing and the quasi-hagiography (which is found only in small sectors of society or from exiles).